Deformation Extraction Method for Roadway 3D Laser Point Cloud Data - ZHAO Bing; MA Bao; HE Bin; XU Shaoyi (Journal of Harbin University of Science and Technology, 2024)
In the process of underground coal resource extraction, the external factors such as high ground pressure and high stress make the surrounding rock shape change and lead to the collapse of the surrounding rock and other phenomena. It will seriously threaten the safety of coal mine production. In order to timely grasp the deformation of surrounding rock in roadway and effectively monitor the deformation of coal mine roadway, we propose a method for extracting tunnel sections and analyzing deformation based on 3D laser point cloud technology. The feasibility of this method is verified through simulation experiments in roadway. And the experimental results show that the proposed method can adapt to the complex environment of the roadway, automatically identify the deformation location of the roadway, and use the section extraction method for more accurate deformation analysis. The monitoring surface displacement resolution can reach centimeter level to meet the needs of roadway surface displacement monitoring.